Use of process engineering and life cycle assessment to calculate the environmental impact of butanol production (2018)
Butanol is a product with a wide market, since its uses are abundant both as a solvent or directly as a reactant in the synthesis of different industrial products. In recent years, it has been shown that this product has important characteristics to be used as a biofuel or as a fossil fuel additive, reducing the environmental load on internal combustion engines. One of the main characteristics of butanol is the possibility of being synthesized via biological routes from renewable feedstocks as agroindustrial wastes. This feature offers economic advantages, since the use of waste as a raw material could reduce the overall cost of the process, in addition to generating a large number of jobs in the supply chain. This work presents the production of butanol through ABE fermentation with a Clostridium acetobutylicum strain, using pre-treated sugarcane bagasse as raw material. Different schemes of butanol production were proposed and evaluated technically, economically, environmentally and socially based on process engineering strategies. The process with the best characteristics was selected to perform a complete environmental evaluation through life cycle assessment, and alternatives to improve environmental performance were proposed (Texto tomado de la fuente)